Postsynthetic functionalization of covalent organic frameworks. Issue 1 (20th August 2019) - Yusran, Yusran; Guan, Xinyu; Li, Hui; Fang, Qianrong; Qiu, Shilun
Abstract: Covalent organic frameworks (COFs) have been at the forefront of porous-material research in recent years. With predictable structural compositions and controllable functionalities, the structures and properties of COFs could be controlled to achieve targeted materials. On the other hand, the predesigned structure of COFs allows fruitful postsynthetic modifications to introduce new properties and functions. In this review, the postsynthetic functionalizations of COFs are discussed and their impacts towards structural qualities and performances are comparatively elaborated on. The functionalization involves the formation of specific interactions (covalent or coordination/ionic bonds) and chemical reactions (oxidation/reduction reaction) with pendant groups, skeleton and reactive linkages of COFs. The chemical stability and performance of COFs including catalytic activity, storage, sorption and opto-electronic properties might be enhanced by specific postsynthetic functionalization. The generality of these strategies in terms of chemical reactions and the range of suitable COFs places them as a pivotal role for the development of COF-based smart materials.